2019
DOI: 10.1039/c9ay01478k
|View full text |Cite
|
Sign up to set email alerts
|

A new approach in voltammetric profiling of wines and whiskies based on a useful faradaic signal component

Abstract: In this work, we have demonstrated that voltammetric signals obtained using metallic electrodes in a simple supporting electrolyte constitute an adequate tool for distinguishing wine and whisky samples of various characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…It was then used to construct plots in the principal component space, which allows simple and reliable distinction of studied objects. 78…”
Section: In-situ Activated Bulk Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was then used to construct plots in the principal component space, which allows simple and reliable distinction of studied objects. 78…”
Section: In-situ Activated Bulk Electrodesmentioning
confidence: 99%
“…Those metal pieces were then mechanically joined with the locksmith table vices. 78 A similar construction with two discs of 1.0 mm diameter, made from GC, placed on the side surface was also reported. 18 The bi-Disc Glassy Carbon Electrode (b-DGCE) was obtained by placing the GC rod in the silver guidewire and covering this construction with the epoxy resin (Fig.…”
mentioning
confidence: 95%
“…A study demonstrated that voltammetric signals obtained using metallic electrodes in a simple supporting electrolyte constitute an adequate tool for distinguishing wines and Scotch whiskies (Wójcik et al., 2019). The study demonstrated that profiling was possible if the faradaic component of the differential pulse voltammetry (DPV) signal was used while disregarding the capacitive charging current.…”
Section: Electroanalytical Techniquementioning
confidence: 99%
“…A chemometric algorithm that works in three‐dimensional space (alternating trilinear decomposition), as well as the DPV technique, was used for the decomposition of the total current recorded. In addition, in comparison with the platinum disk electrode, the construction and operation of the quadruple‐disk iridium electrode (an environmentally friendly voltammetric sensor) was presented (Wójcik et al., 2019). It was observed that when the disturbing and non‐informative capacitive current were rejected, an optimal effect in profiling was achieved.…”
Section: Electroanalytical Techniquementioning
confidence: 99%
“…Based on the differential pulse voltammetry technique's selected current component, Wójcik et al [136] employed voltametric sensors to profile wine and Scotch whisky samples with a complicated composition using voltametric sensors. This novel technique has the potential to represent a significant step forward in the development of voltametric complicated sample profiling, as well as the fabrication of electronic tongues.…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%